SENSE OF SELF-EFFICACY AND STYLES OF COPING STRESS OF YOUNG SPECIAL NEEDS TEACHERS - Czyż, Anna Katarzyna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The author presented the results of research on the sense of self- efficacy and styles of coping with stress young special needs teachers, who take cooperation with people with disabilities, and who are obliged to cope with adversity and to help in the fight against distress their dependents. Research conducted in quantitative strategies, using the normalized and standardized tests: GSES - Generalized Self - Efficacy Scale by Schwarcer and Jerusalem in Polish adaptation by Schwarcer, Jerusalem and Juczyński, and CISS - Coping Inventory for Stressful Situation by Endler and Parker, in Polish adaptation by Strelau, Jaworowski, Wrześniewski and Szczepaniak from 2009.